Cultivating Pupils’ Religious-Ecological Attitudes Through Faith-Based Eco-Education in Disaster-Prone Areas: Impacts and Implementation Factors - Arifin, Anugrah; Sukarta (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to examine the effectiveness of an Islamic and Muhammadiyah movement (AIK)-based eco-education programme in enhancing pupils’ religious-ecological attitudes in disaster-prone areas and to identify the supporting and hindering factors. A mixed-methods sequential explanatory design was employed, consisting of a one-group pretest–posttest experiment involving 30 pupils at SMPN 12 Mataram, located along the banks of the Jangkok River, followed by in-depth interviews with teachers, the headteacher, and pupils. The post-test instrument demonstrated acceptable internal consistency (Cronbach’s alpha = 0.645), although only 5 of the 20 items were found to be valid. The results showed an increase in the mean score from 58.5 at pre-test to 64.8 at post-test. A paired-samples t-test indicated that this increase was statistically significant (t(29) = 2.60, p < 0.05), with a moderate effect size (Cohen’s d = 0.47), indicating a meaningful practical impact. The qualitative findings further demonstrated that the internalisation of the values of khalifah, maslahah, and the prohibition of isrāf through habitual practices, such as the “Clean Friday” programme, strengthened pupils’ awareness that environmental protection is an integral part of religious faith. However, challenges, including limited resources and inadequate parental support, remained. This study contributes a contextually integrated model of AIK and eco-education for flood-prone schools. The practical implications include strengthening the curriculum through fiqh al-bi’ah, providing continuous teacher training, and developing standardised evaluation instruments to support spiritually grounded disaster-mitigation education.